2021
DOI: 10.3390/app11062682
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ultrasound Accuracy in Acute Appendicitis Diagnosis

Abstract: Acute appendicitis it a quite common abdominal disorder and considered as a difficult diagnosis. An accurate diagnosis is essential to prevent any complication from delayed surgical intervention. Aim: To evaluate the diagnostic accuracy of ultrasound in acute appendicitis cases in Saudi Arabia compared with histopathology. Moreover, to determine whether there is a correlation between the accuracy of ultrasound in acute appendicitis and the sonographers’ expertise. Methods: A retrospective study was conducted, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Ahmed and co-workers (2016) also demonstrated comparable findings with a US accuracy of 84%, sensitivity of 86%, and specificity of 80% [10]. On the other hand, Alelyani and co-workers (2021) reported some inconsistent trends in which the US accuracy and sensitivity are relatively lower at 46.2% and 38.9%, respectively, but with a specificity of 89.5% [15].…”
Section: Discussionmentioning
confidence: 86%
“…Ahmed and co-workers (2016) also demonstrated comparable findings with a US accuracy of 84%, sensitivity of 86%, and specificity of 80% [10]. On the other hand, Alelyani and co-workers (2021) reported some inconsistent trends in which the US accuracy and sensitivity are relatively lower at 46.2% and 38.9%, respectively, but with a specificity of 89.5% [15].…”
Section: Discussionmentioning
confidence: 86%
“…The authors concluded that not only can ultrasonography image all inflamed appendices but also can predict the severity of disease with high sensitivity. On the other hand, cases of acute appendicitis diagnosed using ultrasound showed a low diagnostic accuracy in other retrospective studies[156,157]. Interestingly, the diagnostic specificity of ultrasound for appendicitis appears to be contradictory, with some studies demonstrating high specificity ranging from 90% to 100% in differentiating perforated from non-perforated appendicitis in children[158], while others reported lower specificity values (33.33%) in a mixed population of adults(25) and children(47) [157].…”
mentioning
confidence: 97%